Health Insurance Financing: A Comparison Study of Insurance Between Indonesia and Malaysia - Mohd Shahril Ahmad Razimi; Anisa Trixie Aurora; Fira Julia; Nissa Alya Salsabilla (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
This paper discusses the obligation of PT. Asuransi Astra Buana in Motor Vehicle Insurance. The goal is to discover the shape of an obligation of PT. Asuransi Astra Buana for Motor Vehicles and recognize the Insurance Claim Process at PT. Asuransi Astra Buana. Via way of means of studying and decoding library substances that exist withinside the literature, the Legislative Invitations, and provisions regarding coverage agreements. Data used on this examination is secondary data, after which accomplished a qualitative analysis. The effects of this examination are PT. Asuransi Astra Buana need to be accountable to the insured who has participated in motor car coverage due to the fact it's miles sure via way of means of the agreement, particularly in Article 1 paragraph (1) of Law Number 40 of 2014 regarding Insurance, PT. Asuransi Astra Buana is obliged to offer the obligation to the insured if withinside the implementation of repayment the insurer will remember the top rate this is nevertheless owed for the continuing coverage duration for the car, the insured need to deliver the insurer the possibility to test the harm earlier than repairing or changing the car, the insured need to observe the provisions that are according with the process via the stairs that need to be executed on the time of filling out the shape need to be authentic and sincere due to the fact in case you make the slightest mistake then the declare submission will maximum probably be canceled. The end of this study is PT. Asuransi Astra Buana is obliged to offer repayment withinside the policy.